2011
DOI: 10.4236/lce.2011.22012
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Regulation and R&D Activity:A Study of the Top Runner Program in Japan

Abstract: The Top Runner Program, a new approach to enhancing the energy efficiency of appliances and vehicles, has been introduced in Japan. In this paper an empirical analysis of the impact of the program and the labeling systems on firms' R&D efforts is carried out. The results show that the Top Runner Program and the labeling system for appliances led to increases in R&D expenditures by appliance producers. The program combined with the labeling system caused a 9.5% increase in appliance producers' R&D expenditures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Also policies to increase the efficiency of consumer products are key for transitions (e.g. Japan's top runner policy) (Hamamoto, 2011). Having recognized their future global market potential, many countries are attempting to be pioneers in low carbon technologies, and support the establishment of domestic lead markets, such as for solar PV or onshore wind (Quitzow et al, 2014).…”
Section: Enter Agency: From Emergent To Governed Energy Transitionsmentioning
confidence: 99%
“…Also policies to increase the efficiency of consumer products are key for transitions (e.g. Japan's top runner policy) (Hamamoto, 2011). Having recognized their future global market potential, many countries are attempting to be pioneers in low carbon technologies, and support the establishment of domestic lead markets, such as for solar PV or onshore wind (Quitzow et al, 2014).…”
Section: Enter Agency: From Emergent To Governed Energy Transitionsmentioning
confidence: 99%
“…Lanoie et al (2008) also verified the positive effect of the environmental regulation by empirically studying the relationship between the environmental regulation and TFP in Quebec's manufacturing industry. Hamamoto (2011) took a new program launched in Japan to improve the energy efficiency of household appliances and automobiles as a natural experiment to analyze its impact on the R&D behavior of enterprises. It was found that the introduction of this program significantly increased the R&D expenditure of household appliances enterprises by 9.5%.…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory follow up is to set standards following the top runner, pressing laggards out of the market. The very differentiated top runner structure for cars, in many weight classes showed an adverse effect in statistical analysis according to (Hamamoto 2011). It is not sure for cultural reasons if such programs can effectively be introduced in the EU.…”
Section: Directing Private Technologies and Behaviormentioning
confidence: 99%
“…The Top Runner in the market receives broad public attention and an exclusive label for a limited period. This leads to a price premium (Nishitani and Itoh 2014), creating an effective incentive for R&D for the firms in the market for electric appliances, see (Hamamoto 2011). The regulatory follow up is to set standards following the top runner, pressing laggards out of the market.…”
Section: Directing Private Technologies and Behaviormentioning
confidence: 99%